Isolation and characterization of Listeria monocytogenes from environmental and clinical sources by culture and PCR-RFLP methods - Meghdadi, Hossein (Iran J Microbiol, 2019)
BACKGROUND AND OBJECTIVES: Due to the widespread distribution of Listeria monocytogenes in environmental and animal sources and serious clinical complications in human, this study was aimed to isolate L. monocytogenes from water and clinical specimens by culture and PCR methods and to investigate the presence of hlyA and inlA virulence genes. MATERIALS AND METHODS: Water and clinical samples of vaginal and fecal were screened for the presence of L. monocytogenes by phenotypic and standard biochemical tests. PCR amplification was performed on extracted DNA using primers based on the hlyA and inlA genes. A 733-bp fragment of inlA gene was used for investigation of polymorphism using RFLP analysis. RESULTS: In total, 45 phenotypically and molecularly confirmed L. monocytogenes strains were isolated from different sources including 30 (16.7%) from water, 9 (11.3%) from vaginal swabs and 6 (7.5%) from fecal samples. RFLP analysis of PCR products using AluI and Tsp509I restriction enzymes, generated two profiles with 8 to 10 bands ranging in size from 15 to 210 bp. The majority of water and clinical isolates were classified in profile 2. CONCLUSION: We demonstrated 45 L. monocytogenes isolates from tested water and clinical samples by phenotypic and molecular tests. The majority of the isolates were classified in the same RFLP profile, showing the water as a potential source of clinical complications in patients in the region of study.